Biodiversidade em Sistemas Agroflorestais implantados em ecorregiões tropicais: uma revisão sistemática - Ortolan, Ezequiel (2024)
Agroforestry systems (AFSs) enable food production while potentially conserving biodiversity, but it is still unknown how AFSs’ characteristics, matrix, and ecoregion where they are located affect their diversity. This study aims to provide a comprehensive characterization of AFSs originated from areas with alternative land use (ALU) and natural vegetation (NV), as well as to understand biodiversity patterns in these AFSs. We conducted a systematic review of papers that compare the biodiversity between AFSs and reference vegetation areas located at tropical ecoregions. Data from 92 papers totalling 294 data sampling sites enabled us to detect a striking difference between ALU and NV AFSs, such as crop type, management strategy, matrix, and ecoregion where they are located. Additionally, both ALU and NV AFSs had lower tree basal area and canopy cover than the reference areas. We also tested the effect of AFSs and reference areas on the species richness of invertebrates, vertebrates, and plants using generalized linear mixed models (GLMM). We did not find an effect of AFSs on vertebrate richness and, interestingly, only NV AFSs showed a negative effect on invertebrate richness. Plant richness was lower in both ALU and NV AFSs. Last, we tested the effects of AFSs’ characteristics, matrix, and ecoregion on species richness using GLMM. The factors affecting species richness varied between ALU and NV AFSs, and among plants, invertebrates, and vertebrates. However, in general, biodiverse AFSs, crop types that form more complex vegetation structure, less intensive management, and more permeable matrices had positive effects on species richness. The effect of ecoregions did not follow the expected according to the natural species richness of the ecoregions. We conclude with directions for future studies and suggestions for more biodiversity friendly ALU AFSs. Importantly, we advocate for the strict prohibition of AFS implementation in areas with preserved native vegetation due to the negative effects on plant and invertebrate communities.